Spinel copper ferrite nanoparticles: Preparation, characterization and catalytic activity. (29th June 2018) - Amini, Mojtaba; Kafshdouzsani, Maryam Hosseinpour; Akbari, Ali; Gautam, Sanjeev; Shim, Cheol‐Hwee; Chae, Keun Hwa
Abstract : The magnetic CuFe2 O4 nanoparticles have been synthesized and characterized by various spectroscopic methods, including X‐ray diffraction (XRD), O K, Cu and Fe K ‐edge X‐ray absorption near edge structure (XANES), energy dispersive X‐ray analysis (EDX), scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The azide‐alkyne cycloaddition by the reaction of various phenylacetylenes with a mixture of benzyl halides and NaN3 and also three component (A 3 ) coupling reaction of aldehyde, alkyne and amine catalyzed by CuFe2 O4 nanoparticles under aerobic conditions led to the formation of the 1, 4‐disubstituted‐1, 2, 3‐triazoles and propargylamines in excellent yields. The catalyst can be recovered by applying an external magnetic field for the subsequent cycloaddition reactions and reused without any tangible loss in catalytic efficiency. Abstract : The azide alkyne cycloaddition and one‐pot three‐component (A 3 ) coupling of aldehydes, amines, and alkynes to the formation of the 1, 4‐disubstituted‐1, 2, 3‐triazoles and propargylamines respectively were conducted by the magnetic CuFe2 O4 nanoparticles.